Analyzing Occupational satisfaction in physical educators in secondary schools/ Al Resafa Education Directorate - Hafed, Hussein; Abulwaheed, Ali (Journal of Physical Education, 2021)
The research aimed at designing an occupational satisfaction scale in secondary school physical educators in Al Rasafa education directorate as well as identifying the level of occupational satisfaction in secondary school physical educators. The researcher used the descriptive method on (433) physical educators on a pilot study, adaptation, application. The data was collected and treated using proper statistical operations to conclude that the occupational satisfaction scale was easy to apply and understand by physical educators. Finally, the researchers recommended providing a healthy environment for physical educators in schools to encourage creativity and making similar studies on other subjects and other grades.